Synthesis of Au@TiO2 core–shell nanoparticles with tunable structures for plasmon-enhanced photocatalysis. Issue 11 (25th October 2019) - Chen, Tian-Ming; Xu, Ge-Yang; Ren, He; Zhang, Hua; Tian, Zhong-Qun; Li, Jian-Feng
Abstract : Au@TiO2 core–shell nanocomposites with tunable morphology, shell thickness, and crystallinity are developed as effective catalysts for plasmon-enhanced photocatalysis. Abstract : Plasmonic metal–semiconductor nanocomposites, especially those with core–shell nanostructures, have received extensive attention as they can efficiently expand light absorption and accelerate electron–hole separation thus improving the photocatalytic efficiency. However, controlled synthesis and structure manipulation of plasmonic metal–semiconductor nanocomposites still remain a significant challenge. Herein, a simple and universal method has been developed for the preparation of plasmonic Au@TiO2 core–shell nanoparticles. Using such a method, uniform TiO2 shells are successfully coated on Au nanoparticles with various morphologies including nanorods, nanocubes, and nanospheres, and the thickness and crystallinity of the TiO2 shell can be simply tuned by adjusting the pH value and thermal treatment, respectively. Furthermore, the influence of the morphology of the Au core and the thickness and crystallinity of the TiO2 shell on the photocatalytic performance of Au@TiO2 towards the photodegradation of methylene blue is systematically explored. It is found that Au@TiO2 NPs with nanorod morphology and crystalline TiO2 shells display the best performance, which is 5 times higher than that of bare Au nanoparticles. This work provides a facile strategy for the fabrication of plasmonic core–shell nanostructures that show excellent performance in plasmon-enhanced photocatalysis.